Strengthening Partnership Ecosystems to Foster Innovation and Empower Farmers Based on Regional Potential in Riau Province - M. Alkadri Perdana; Andri Nofiar. Am; Anggy Trisnadoli; Hardiyanto Hardiyanto; Johny Custer; Elvi Rahmi (Jurnal Penelitian Pendidikan IPA, 2025)
In the face of rapid economic and technological change, building a robust partnership ecosystem is essential to ensure inclusive and sustainable development, particularly in regions with strong resource-based economies such as Riau Province, Indonesia. As the largest palm oil–producing region in the country, Riau plays a pivotal role in Indonesia's agricultural landscape. However, its significant economic growth—mainly driven by the palm oil industry—has not translated into equitable outcomes for rural communities, especially smallholder farmers and the sustainability of education for farmers' children. This study aims to develop an integrated framework that strengthens multi-stakeholder partnerships to foster innovation and empower farmers based on regional potential. The research adopts foresight methodology and system dynamics to model strategic scenarios. Data were analyzed through horizon scanning, focus group discussions, and simulation techniques. The results highlight persistent gaps in employment absorption, rural unemployment, and limited access to innovation and vocational training. Over half of surveyed enterprises indicated plans to enhance digital infrastructure and adopt artificial intelligence (AI). The study concludes that inclusive partnerships, vocational education aligned with industrial needs, and technology adoption are key to empowering farmers, diversifying the economy, and enhancing regional resilience.